(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2021)
In 2018, the Federal Network for Professional, Scientific and Technological Education completed a decade of existence. Established under Law No. 11,892/2008, the network brings together several institutions that, together, offer 495,682 enrollments at secondary level (BRASIL, 2017), a modality in which secondary education must be articulated with preparation for the world of work. In this context, this theoretical essay aims to understand how the marks of the duality between basic education and professional training are manifested in Critical Mathematics Education (CME) and in Middle Level Technical Professional Education (EPTNM), with a view to understanding similarities and divergences between EPTNM and EMC, particularly with regard to curriculum and teaching. Mathematics must be taught as a necessary science for solving real problems and for a critical perception of the world of work.